We have sum_(k=1)^n(2n+1)/(n+k+1)^2 le sum_(k=1)^n(2n+1)/((n+k+1)^2-1) but
1/((n+k+1)^2-1) = 1/2(1/(n+k)-1/(n+k+2)) and
sum_(k=1)^n1/((n+k+1)^2-1) = 1/2(1/(n+1)+1/(n+2)-1/(2n+1)-1/(2n+2)) or more compactly
sum_(k=1)^n1/((n+k+1)^2-1) =1/4(4n^2+5n)/(2 n^3 + 7 n^2+ 7 n+2)
now we have
lim_(n->oo)sum_(k=1)^n(2n+1)/((n+k+1)^2-1)=lim_(n->oo)1/4((2n+1)(4n^2+5n))/(2 n^3 + 7 n^2+ 7 n+2) = 1
so
lim_(n->oo)sum_(k=1)^n(2n+1)/(n+k+1)^2 le 1
or
lim_(n->oo)sum_(k=0)^n(2n+1)/(n+k+1)^2-lim_(n->oo)(2n+1)/(n+1)^2 le 1 so
lim_(n->oo)sum_(k=0)^n(2n+1)/(n+k+1)^2 le 1
Now int_(xi=0)^(xi=n) (d xi)/(n+xi+1)^2 le lim_(n->oo)sum_(k=0)^n 1/(n+k+1)^2
but
int_(xi=0)^(xi=n) (d xi)/(n+xi+1)^2 =1/(n+1)-1/(2n+1) and
lim_(n->oo)(2n+1)(1/(n+1)-1/(2n+1))=1
so
1 le lim_(n->oo)sum_(k=0)^n(2n+1)/(n+k+1)^2 le 1 and concluding
lim_(n->oo)sum_(k=0)^n(2n+1)/(n+k+1)^2=1